PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP PENGETAHUAN FAKTUAL DAN KONSEPTUAL SISWA KELAS V SD - Listiani, Oetary; Widi Winarni, Endang; Koto, Irwan (Jurnal Kajian Pendidikan Dasar, 2025)
The aim of this research is to analyze the effect of science learning using the Discovery Learning model assisted by audio-visual media on factual and conceptual knowledge. The type of research used is quasi-experimental research using a pretest-posttest control group design. The type of data used is quantitative data, namely using question instruments and expert validation sheets. Based on the results of the hypothesis test, it was found that the application of science learning using the Discovery Learning model assisted by audio-visual media had a significant effect on factual and conceptual knowledge. The N-Gain test on the factual knowledge of the experimental class was 93% in the effective category, while in the control class it was 34% in the ineffective category. Knowledge of the concept of the N-Gain test in the experimental class was 86% in the effective category and 26% in the control class in the ineffective category. The correlation test shows there is no significant relationship between factual and conceptual knowledge. The application of science learning using the Discovery Learning model assisted by audio-visual learning media has a significant effect on context knowledge. This is demonstrated by the posttest average of conceptual knowledge in the control class being 54. Meanwhile for the experimental class the average result is 91. Furthermore, there is no relationship between the dimensions of factual knowledge and conceptual knowledge in science learning using the Discovery Learning model assisted by audio-visual media.